Landscape of immune infiltration in entorhinal cortex of patients with Alzheimerʼs disease - Zhang, Hui; Cao, Silu; Xu, Yaru; Sun, Xiaoru; Fei, Miaomiao; Jing, Qi; Xu, Xiaodong; Tang, Jinxuan; Niu, Bing; Li, Cheng (Frontiers in Pharmacology, 2022)
Alzheimer's Disease (AD) is one of the most common neurodegenerative disease, manifesting as progressive memory loss and cognitive dysfunction. Neuroinflammation plays an important role in the development of AD, and anti-inflammatory drugs have been reported with the function of reducing the risk of the disease. However, the immune microenvironment in the brain is remains unclear, and the mechanisms of anti-inflammatory drugs reducing AD have not been clearly revealed. This study aimed to provide an overview of immune cell composition of the entorhinal cortex in patients with AD based on the transcriptomes and signature genes of different immune cell, and to explore potential therapeutically meaningful targets based on the relevance of drug target. Transcriptomic data extracted from entorhinal cortex, derived from GSE118553, were used to support our study. We compared the differently expressed immune-related genes between ADs and controls by using the limma package. And, the difference in immune cell composition between Alzheimer's Disease patients (ADs) and controls was detected with xCell algorithm based on the marker genes in immune cells. Correlation between marker genes and immune cells was conducted to explore the potential genes that cause the difference between the two groups. Through the correlation between marker genes and immune cells, as well as the interaction between gene-drug targets to explore potential therapeutic target genes and drugs. Differentially expressed gene analysis revealed 81 immune-related differentially expressed genes (irDEGs) between ADs and controls, and they participated in several immune-related pathways. xCell analysis showed that most lymphocyte cells were decreased in ADs, including CD4+ Tc cells, CD4+ Te cells, eosinophils, Th1 cells, NK cell, NKT, Pro B cells and Tregs, except for Th2 cells. In contrast, most of the myeloid cells had elevated in ADs, except for DC cells. They were basophils, mast cells, plasma cells and macrophages. Correlation analysis suggested that 37 genes were associated with these cells involved in innate immunity, of which 8 genes were drug targets. Taken together, these results delineate the profile of the immune components of the entorhinal cortex in ADs, providing a new perspective on development and treatment of AD.